Kajian Hasil Belajar Taruna Teknik Pesawat Udara Menggunakan Problem Based Learning Method di Akademi Teknik dan Keselamatan Penerbangan Makassar - Nur, Mulyadi (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2019)
The aviation engineering and safety academy is a high school under the Indonesian Ministry of Transportation, with the main task of carrying out a professional Diploma program in aviation engineering and safety expertise that is open to the public. Makassar ATKP has two educational programs specifically in the Aircraft Engineering Study Program, namely Diploma and Non-diploma education. The curriculum used in educating participants in the Aircraft Maintenance Technology Study Program is 70% Practice and 30% Theory and refers to the Curriculum and Syllabus provided by BPSDM (Human Resources Development Agency) Air Transportation, DIKTI and DKUPPU (Directorate of Airworthiness) and Aircraft Operations). According to the statistical results we can conclude there is a change in the achievement of results / values ​​obtained by each student of the ND TPPU study program class II. Where is Tar.3 in the name of Al Imran Hamiluddin. HR, Tar.4 on behalf of Andi Sultang, Tar. 5 on behalf of Andriani and Tar.8 on behalf of Aswar alrafi Risqullah experienced a pretty good increase in scores, while twenty other students experienced a significant decrease. This happens due to a change in the methodology system experienced by the study group.